Response of Frankliniella occidentalis and Thrips tabaci to thrips lures in California - Nielsen, M-C.; Butler, R.C.; Teulon, D.A.J. (New Zealand Plant Protection, 2016)
Two field trials were undertaken in a fallow field adjacent to citrus trees at Agricultural Operations at the University of California Riverside (CA) USA to examine the efficacy of 14 chemical lures for attracting western flower thrips (WFT) Frankliniella occidentalis (Pergande) and onion thrips (OT) Thrips tabaci Lindeman to yellow sticky traps over 24 hours Air temperatures during the two trials ranged from 16 to 36oC In both trials traps with methyl isonicotinate caught significantly more (x28 and x34 respectively) female WFT than traps without lures No other chemical lure tested caught as many WFT as the methyl isonicotinatebaited traps In trial 1 traps with ethyl isonicotinate (not included in bioassay 2) caught significantly more female OT (x40) than traps without lures No other chemical lure tested caught as many OT as the ethyl isonicotinatebaited traps Because of the close proximity of the traps (10 m between traps) control traps were expected to have been influenced by odour from baited traps thereby reducing the apparent efficacy of the baited traps